YARNING AS PROTECTED SPACE: principles and protocols. (June 2020) - Barlo, Stuart; Boyd, William (Bill) Edgar; Pelizzon, Alessandro; Wilson, Shawn
Traditional methods of imparting knowledge are known as yarning to Australian Aboriginal Elders and talking circles to North American First Nations peoples. Yarning is a relational methodology for transferring Indigenous knowledge. This article describes an emerging research methodology with yarning at its core, which provides respect and honour in a culturally safe environment. Yarning is highly structured, with protocols and principles providing participants control over the process and their stories. The methodology is embedded in a yarning space, which is framed by six protocols and seven principles. The protocols are gift, control, freedom, space, inclusiveness and gender specificity, and the principles are reciprocity, responsibility, relationship, dignity, equality, integrity and self-determination—to protect participants, stories and data. This is ensured through respectful and honouring relationships, responsibility and accountability between participants. The key camps in which the yarning journey is segmented are the Ancestors, protocols, principles, connections, data, analysis, processing and reporting, and the wider community.